Non-selected reflexive datives in Southern American and Appalachian English vs. Spanish - Teomiro García, Ismael Iván (Estudios Ingleses de la Universidad Complutense, 2013)
Southern American and Appalachian English allow the occurrence of non-selected reflexive datives (I need me some water) unlike Standard American and British English. This kind of non-selected arguments looks similar to ethical datives in some Romance languages like Spanish (Este nino no me come nada). However, non-selected reflexive datives have structural differences in Southern American and Appalachian English in comparison with Spanish. This paper sets out to look at these languages (Southern American and Appalachian English vs. Spanish), and describe the syntactic and semantic similarities and differences of non-selected reflexive datives across them. Finally, a theoretical analysis is sketched within the framework of Generative Grammar in order to explain some of such differences and similarities.